2022
DOI: 10.1002/tox.23586
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 exposure‐induced ferroptosis in neuronal cells via inhibiting ERK/CREB pathway

Abstract: PM 2.5 exposure has been demonstrated to correlate with neurological disorders recently. Ferroptosis is recognized as a newly found programmed form of cell death associated with neurodegenerative diseases, while glutathione peroxidase 4 (GPX4) is a key regulator of ferroptosis. However, the relationship between PM 2.5 -induced neurotoxicity and ferroptosis is still unclear. The current study aims to investigate if ferroptosis is involved in neurotoxicity post PM 2.5 exposure and its underlying mechanism. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 67 publications
(125 reference statements)
2
17
0
Order By: Relevance
“…Wang et al have affirmed that CREB directly binds the promoter of GPX4 in H1299 cells via ChIP experiments [ 22 ]. Xiong et al demonstrated that PM2.5 exposure induces ferroptosis in neuronal cells by inhibiting CREB [ 40 ]. Chen et al indicated that the bioflavonoid galangin delivered its anti-ferroptosis effects by activating CREB in a hepatic ischemia‒reperfusion model [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al have affirmed that CREB directly binds the promoter of GPX4 in H1299 cells via ChIP experiments [ 22 ]. Xiong et al demonstrated that PM2.5 exposure induces ferroptosis in neuronal cells by inhibiting CREB [ 40 ]. Chen et al indicated that the bioflavonoid galangin delivered its anti-ferroptosis effects by activating CREB in a hepatic ischemia‒reperfusion model [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“… 77 In an another study, FPM exposure would lead to ferroptosis in neuronal cells by inhibiting the extracellular regulated protein kinases (ERK)/cAMP-response element binding protein (CREB) pathway. 78 …”
Section: Major Cell Death Pathways Induced By Fine Particulate Mattermentioning
confidence: 99%
“…g ., As, Pb and Cd, could induce imbalances in redox systems, thereby causing ferroptosis . In an another study, FPM exposure would lead to ferroptosis in neuronal cells by inhibiting the extracellular regulated protein kinases (ERK)/cAMP-response element binding protein (CREB) pathway …”
Section: Major Cell Death Pathways Induced By Fine Particulate Mattermentioning
confidence: 99%
“…9,10 Ferroptosis is triggered through the inactivation of antioxidant defenses by dependent cellular glutathione (GSH), resulting in the increase of toxic lipid reactive oxygen species. 11 Evidence has determined that the ferroptosis is involved in a variety of pathological injuries, such as nickel oxide nanoparticles-induced acute lung injury, 12 1,3-DCP-induced hepatocytes injury, 13 hexavalent chromium-induced testicular injury, 14 PM2.5-induced neurological injury, 15 and cadmium-induced neurological injury. 16 In addition, ferroptosis also participates the progression of various cancers, including nasopharyngeal carcinoma, 17 gastric cancer, 18 colorectal cancer, 19 glioblastoma, 20 acute myeloid leukemia, 21 and trastuzumab-resistant breast cancer.…”
Section: Introductionmentioning
confidence: 99%